2012
DOI: 10.1007/s11999-012-2293-8
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty Versus Hemiarthroplasty for Displaced Femoral Neck Fractures: Meta-analysis of Randomized Trials

Abstract: Background Most patients with displaced femoral neck fractures are treated by THA and hemiarthroplasty, but it remains uncertain which if either is associated with better function and lower risks of complications. Questions/purposes We performed a meta-analysis of randomized controlled trials (RCTs) to determine whether THA was associated with lower rates of reoperations, mortality, complications, and better function compared with hemiarthroplasty. Methods We searched the PubMed, Embase, Chinese Biomedicine Li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
108
5
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 139 publications
(128 citation statements)
references
References 35 publications
(84 reference statements)
12
108
5
3
Order By: Relevance
“…They also found indications of better functional outcome following total hip replacement compared to hemiarthroplasty ). The latter has been supported by two recent meta-analyses (Hopley et al 2010, Yu et al 2012). However, a recently published long-term follow up of a randomized controlled trial found that patients with mental impairment who received total hip replacement had a complication rate of 16% similar to the patients treated by internal fixation for a displaced femoral neck fracture (Johansson 2014).…”
Section: Prosthetic Replacementmentioning
confidence: 68%
“…They also found indications of better functional outcome following total hip replacement compared to hemiarthroplasty ). The latter has been supported by two recent meta-analyses (Hopley et al 2010, Yu et al 2012). However, a recently published long-term follow up of a randomized controlled trial found that patients with mental impairment who received total hip replacement had a complication rate of 16% similar to the patients treated by internal fixation for a displaced femoral neck fracture (Johansson 2014).…”
Section: Prosthetic Replacementmentioning
confidence: 68%
“…Hip fractures in older patients are associated with impaired mobility, excess morbidity and mortality and obvious loss of independence [2,3]. It is estimated that the annual medical costs owing to hip fractures will be more than US $15 billion at this time [4].…”
Section: Introductionmentioning
confidence: 99%
“…There is much evidence supporting THA for treatment of femoral neck fractures in active elderly patients [3,11,15,21,22]. However, we found that patients undergoing THA for femoral neck fracture were more likely to die within 30 days of surgery, experience a major postoperative medical complication, have a reoperation, stay in the hospital longer, and be discharged to a postacute care facility than were patients undergoing THA for OA.…”
Section: Discussionmentioning
confidence: 58%
“…However, more recent evidence emphasizes the functional advantages of THA over hemiarthroplasty in the treatment of femoral neck fractures in active elderly patients [3,11,15,21,22]. Additionally, in patients who develop a painful hemiarthroplasty, conversion of hemiarthroplasty to THA is more difficult and associated with more complications than a primary THA for osteoarthritis (OA) [19].…”
Section: Introductionmentioning
confidence: 99%